Expertise as a leadership process : leadership in future work networks - Leino, Tiina (Nordic Academy of Management, 2019)
At work, I have discovered how meaningful is the process of experts using leadership in managing tasks, work processes and networks. Diverse and continuous processes between different actors in different projects are constantly evolving. In practice, actions and achievements in meeting goals in different projects are very different. In my research I aim to add new knowledge to the work processes of experts and I aim to look the processes from the perspective of leadership. The focus of the research is on people working in expert positions and who lead processes and networks of people regarding their work responsibilities and goals. New ways of organizing work are emerging both in organizations and in networks. The results of the research can be used to renew leadership in organizations.
Keywords: expert; leadership; work process; fi=Johtaminen ja organisaatiot|en=Management and Organization|